PERUBAHAN SIFAT FISIK GAMBUT AKIBAT KEBAKARAN DI DESA TELUK BINJAI KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN - Muhamad Tahrun; Wawan '; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research is conducted to compare the physical characteristic change between burnt & unburnt peat soil and also to understand its change on both seven days & four months after burn. This research is held in “Teluk Binjai Village, District ofTeluk Meranti, Regency ofPelalawan” and its physical analysis is held at Soil Science Lab of Riau University Agricultural Faculty on January until June 2014. Moreover, it uses survey method to determine its location and purposive sampling for sampling method. Both peat soil sampling & field observation are done twice. First sampling is conducted on seven days after burn and the second sampling is done four months later (after burn). Its data analyzed by using descriptive statistic and presented on tables & graphs. In addition, the observed parameters are Particle Size Distribution (PSD), water holding-capacity, Bulk Density (BD), Particle Density (PD), porosity and permeability. The results show that fire on peat land causes physical characteristic change on peat soil with the sign of decreasing on water holding-capacity, porosity and permeability. Meanwhile, both Bulk Density (BD) and Particle Density (PD) are increasing on the burnt rather than the unburnt one. Physical characteristic change of peat soil from seven days until four months after burn causes re-increasing on water holding-capacity, porosity and permeability at the depth of 10-20 cm. Moreover, there are increasing on fine particle size (88 µm and 106 µm) at the depth of 10-30 cm and increasing on both Bulk Density (BD) & Particle Density (PD) at the depth of 20-25 cm. Keywords: Fire, Physical Characteristic, Peat Soil